A ten-year survey of software architecture - Yao Chen; Xiaoqing Li; Lingyun Yi; Dayong Liu; Liu Tang; Hongli Yang (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
A software architecture can be described as the "blueprint" of a system at the highest level of abstraction, describing components and their important interconnections. In this paper, we retrospectively examine advances and achievements in software architecture during the last ten years, including software architecture description languages, design, analysis and evaluation, evolution and service-oriented architecture. Finally, we discuss the promising research directions on software architecture.